Pengaruh Tax Planning, Kebijakan Hutang dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Sektor Basic Materials yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2024 - Selvia Selvia; Sandra Dewi (Lembaga Yasin AlSys, 2026)
Firm value is an important indicator that reflects investors’ perceptions of a company’s performance and prospects. Although the relationship between tax planning, debt policy, firm size, and firm value has been widely examined, studies that specifically analyze these three variables in Basic Materials sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period remain limited. This study aims to analyze the effect of tax planning, debt policy, and firm size on firm value. This study used a quantitative approach with a causal associative design. The sample consisted of 18 companies selected using purposive sampling, resulting in 61 observations after outlier elimination. Data were collected through documentation of companies’ annual financial reports and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 26. The results show that tax planning and firm size have a positive and significant effect on firm value, whereas debt policy has no significant effect. Simultaneously, tax planning, debt policy, and firm size have a significant effect on firm value. These findings contribute to the development of Signaling Theory in explaining the formation of firm value through financial information perceived by investors as market signals. The conclusion of this study emphasizes the importance of the effectiveness of tax planning and firm size in increasing firm value. The implications of this study include theoretical contributions to the development of financial management literature as well as practical implications for company management in formulating strategies to increase firm value. Keywords: Tax Planning; Debt Policy; Firm Size; Firm Value; Basic Materials Sector